2020
DOI: 10.1039/d0sc04520a
|View full text |Cite
|
Sign up to set email alerts
|

2′-O-Trifluoromethylated RNA – a powerful modification for RNA chemistry and NMR spectroscopy

Abstract: New RNA modifications are needed to advance our toolbox for targeted manipulation of RNA. In particular, the development of high-performance reporter groups facilitating spectroscopic analysis of RNA structure and dynamics,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…Presenting all the refined aspects of this topic is beyond the scope of our review. Still, we can mention some recent references focusing on the recombinant production of proteins dedicated to NMR analysis: (i) for a uniform 2 H-, 13 C- and/or 15 N-labeling in E. coli , yeast, , insect cells, or mammalian cells, , (ii) for 13 C-methyl-labeling in E. coli , ,, yeast, or insect cells, (iii) for amino-acid-specific labeling in E. coli , insect cells, (iv) for unnatural amino acids labeling containing 19 F-moieites or other non-natural chemical functions. , The so-called cell-free approaches also offer a variety of isotope labeling possibilities. Concerning the production of nucleic acids for NMR, methods exist and are continuously being developed, using enzymatic reactions for uniformly or nucleic acid-specific 2 H-, 13 C-, and/or 15 N-labeled nucleic acids, or solid-phase synthesis allowing position-specific labeling, ,, or the insertion of non-natural bases like those incorporating 19 F-moieties. 13 C-methyl-labeling of DNA has also been proposed recently . The field is vast though, and we guess that many of the noncited labeling schemes would find interesting applications for in-cell NMR studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Presenting all the refined aspects of this topic is beyond the scope of our review. Still, we can mention some recent references focusing on the recombinant production of proteins dedicated to NMR analysis: (i) for a uniform 2 H-, 13 C- and/or 15 N-labeling in E. coli , yeast, , insect cells, or mammalian cells, , (ii) for 13 C-methyl-labeling in E. coli , ,, yeast, or insect cells, (iii) for amino-acid-specific labeling in E. coli , insect cells, (iv) for unnatural amino acids labeling containing 19 F-moieites or other non-natural chemical functions. , The so-called cell-free approaches also offer a variety of isotope labeling possibilities. Concerning the production of nucleic acids for NMR, methods exist and are continuously being developed, using enzymatic reactions for uniformly or nucleic acid-specific 2 H-, 13 C-, and/or 15 N-labeled nucleic acids, or solid-phase synthesis allowing position-specific labeling, ,, or the insertion of non-natural bases like those incorporating 19 F-moieties. 13 C-methyl-labeling of DNA has also been proposed recently . The field is vast though, and we guess that many of the noncited labeling schemes would find interesting applications for in-cell NMR studies.…”
Section: Methodsmentioning
confidence: 99%
“…These have been shown to be capable to establish new hydrogen bonds through the fluorine atom and to affect the structure in some cases. ,, Consequences on enzymatic capacities have been reported, notably because fluorination affects tyrosine p K a . Some other proteins are not perturbed by the incorporation of fluorinated aromatic amino acids. , The accumulation of too many fluorinated amino acids in hydrophobic cores appears to have destabilizing consequences, and it is advisable to dilute fluorine incorporation, notably for the more abundant phenylalanines. ,,, Most of monofluorinated nucleotides are thought to have only minor consequences on nucleic acids thermodynamic stability, whereas trifluorination might be more deleterious. ,,, …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorination of nucleic acids in a site-specific manner represents an ideal approach for elucidating their structures and functions based on 19 F NMR. [15,[39][40][41][42] We have previously demonstrated that 4'-F-uridine ( 4'-F rU) is an ultrasensitive probe for detecting the secondary structure of RNA. Duplex formation by annealing 4'-F rU-modified RNA with complementary RNA strand leads to a 19 F NMR chemical shift dispersion as large as 4 ppm (compared with < 1 ppm for 2'-F U).…”
Section: Probing the Secondary Structure Of Dna By 4'-f T Modificationmentioning
confidence: 99%